The interaction between self – assembling peptides and emodin and the controlled release of emodin from in-situ hydrogel. Issue 1 (4th December 2019) - Wei, Weipeng; Meng, Cui; Wang, Yuhe; Huang, Yongsheng; Du, Wenbin; Li, Hongfang; Liu, Yanfei; Song, Hong; Tang, Fushan
Abstract: Ion-complementary self-assembling peptides have potential in delivering hydrophobic drugs. This study involved two self-assembling peptides, RADA16-I and RVDV16-I, of which RVDV16-I was a novel self-assembling peptide with different hydrophobic side chains designed from RADA16-I. The purpose of this study was to observe the interaction between different self-assembling peptides and emodin through fluorescence spectrophotometry, CD, SEM and AFM; to construct a preliminary suspension in-situ hydrogel delivery system for emodin with the self-assembling peptides; and to investigate the drug-loading and drug-releasing properties of the self-assembling peptides on emodin. The results showed that both peptides can interact with emodin and the interaction was dominated by hydrophobic interaction. The aqueous solutions of both self-assembling peptides can form relatively stable suspensions with emodin under mechanical stirring, and the suspension can form in-situ hydrogel under physiological condition. In vitro release of emodin from the hydrogels showed a manner of sustained release to some extent. Cell viability studies showed inherent proliferation inhibiting effects of emodin on tumor cells was maintained or enhanced through the in-situ hydrogels. The self-assembling peptides RADA16-I and RVDV16-I had showed promising drug-loading and drug-releasing performance for hydrophobic drugs. It is reasonable to exploit self-assembling peptides as drug carriers for their great potential to improve delivery of hydrophobic drugs.